Bioacustics of Hylarana Celebensis (Peters, 1872) (Anura: Ranidae)From Sulawesi - Kurniati, Hellen (JURNAL BIOLOGI INDONESIA, 2016)
Hylarana celebensis (Peters, 1872) is an endemic frog to Sulawesi, the species being a member of family Ranidae.Â  The presence of the frog in its habitat is easily detected from its advertisement call; males usually call in a chorus, they call to each other in a large group. Bioacoustics of calls that a typical individual male of H. celebensis has not been described in detail, although it is very easy to find this species in freshwater swamps, permanent ponds, or slow-flowing waters in the lowland areas. The purpose of the bioacoustic analysis on H. celebensisâs calls that were recorded at Bahodopi area is to build a reference collection to be compared with H. celebensisâs bioacoustics to the other regions in Sulawesi. Because of the wide distribution of this frog in Sulawesi; population genetic structure of H. celebensis may also follow the population genetic structure of Ingerophrynus celebensis. Calls of H. celebensis have two types of calls, i.e. pure tone and pulse; however, pure tones have three variation, namely pure tone type 1, pure tone type 2 and pure tone type 3; however pulsed call has only one type.Â Keywords: Anura, Hylarana celebensis, bioacoustics, Sulawesi.Â